(untitled) (AYUSHDHARA, 2017)
Ocular allergy is often under-diagnosed but has a significant impact on the quality of life and vision in all ages especially in childhood. Although its incidence varies by geographical location, the prevalence is difficult to gauge as allergies tend to be underreported compounded by the difficulty in classification. Vernal keratoconjunctivitis (VKC) is one of the most commonly occurring types of allergic conjunctivitis. It usually appears in three forms i.e., palpebral, bulbar and mixed and predominantly occurs in younger age group between 4-20 years. This chronic disease is characterized by the formation of giant papillae which constantly irritates the cornea and predispose to ectatic corneal disorders like keratoconus and cause myopia and astigmatism. Topical corticosteroids relieve itching, redness and edema but should be used with caution as their constant use are known to cause glaucoma, cataracts, secondary bacterial; viral and fungal infections and delayed wound healing. In Ayurveda, the disease Vartmasharkara shows clinical features similar to this disease and Acharya Susruta has suggested Chedana followed by Lekhana to manage this condition. This article describes the case report of a 12 year old male child who had complaints of palpebral form of VKC. In the present study, it is observed that Ayurvedic management along with Chedana and Lekhanakarma has provided significant relief in all signs and symptoms of allergic conjunctivitis.